TINJAUAN HUKUM ISLAM TERHADAP PELELANGAN SEWA SAWAH DENGAN SISTEM UNDIAN: (Study Kasus Desa Sukowati Kecamantan Kapas Kabupaten Bojonegoro) - Syaifuddin Farid, M. (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2022)
This study aims to find out how to rent rice fields with a lottery system in Sukowati village, Kapas sub- district, Bojonegoro Regency and find out the views of Islamic law on rice field rental auctions with a lottery system. In this study, the author uses a qualitative method using an empirical juridical approach, deductive and descriptive analysis techniques and then takes informasi sources from village officials based on field facts. The results of the study show that the rent in the village of Sukowati is in accordance with Islamic law and civil law and determines the rights of the tenants with a lottery system with nomor party being harmed in accordance with Islamic law, therefore the author draws the conclusion that the lease with the lottery system in the village Sukowati has complied with Islamic law. Keywords: Islamic Law, Rent, lottery